2022
DOI: 10.1038/s41420-022-01278-w
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase type 2-dependent crosslinking of IRF3 in dying melanoma cells

Abstract: AbstractcGAS/STING axis is the major executor of cytosolic dsDNA sensing that leads to the production of type I interferon (IFNI) not only upon bacterial infection, but also in cancer cells, upon DNA damage. In fact, DNA damage caused by ionizing radiations and/or topoisomerase inhibitors leads to a release of free DNA into the cytosol, which activates the cGAS/STING pathway and the induction of IFNI expression. Doxorubicin-induced apoptotic cancer cells release damage-associated molecular patterns (DAMPs), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In keeping with these findings, newly we showed that, upon doxorubicin treatment (Fig. 1), TG2 translocates into the nucleus and catalyzes the formation of covalent cross-linked IRF3 (Interferon regulatory factor 3) dimers, thereby limiting the production of IFNβ in dying melanoma cells [51].…”
Section: Potential Tg2/cbaf Interplay In Diseasesupporting
confidence: 80%
“…In keeping with these findings, newly we showed that, upon doxorubicin treatment (Fig. 1), TG2 translocates into the nucleus and catalyzes the formation of covalent cross-linked IRF3 (Interferon regulatory factor 3) dimers, thereby limiting the production of IFNβ in dying melanoma cells [51].…”
Section: Potential Tg2/cbaf Interplay In Diseasesupporting
confidence: 80%